Protection and Natural Monopolies - Commons, John R. (Quarterly Journal of Economics, 1892)
Journal Article Protection and Natural Monopolies Get access John R. Commons John R. Commons Oberlin College Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 6, Issue 4, July 1892, Pages 479–484, https://doi.org/10.2307/1882519 Published: 01 July 1892